The Strategic Dimension of Interpreting - Kohn, Kurt; Kalina, Sylvia (Meta, 1996)
AbstractThis article analyses consecutive and simultaneous interpreting from a strategic point of view. A concept of discourse-based mental modelling serves as a basis to describe the cognitive-linguistic processes and strategies underlying comprehension and production in interpreted bilingual communication. By contrast with processing in the monolingual context, the interpreting process is characterised by adverse conditions including above all the lack of semantic autonomy and the continuing presence of elements of the source language during different stages of processing. The strategies interpreters use will therefore necessarily differ from those used in monolingual communication and will be adapted to the specific requirements of the interpreting process. Characteristic difficulties of interpreting and corresponding strategic processes are discussed with reference to the communicative transfer relation between source and target discourse, the sequential organisation of source discourse comprehension and target discourse production in consecutive interpreting, the parallel organisation of source discourse comprehension and target discourse production in simultaneous interpreting, and the complexity of content andlor linguistic representation of the source discourse. In an empirical analysis, a bit of simultaneous discourse is studied along with introspective data on the processes at work during production. The introspective data was obtained by means of a retrospective thinking-aloud protocol. Product-related and process-related data indicate that the strategies discussed are used in real-life interpreting situations.